2016
DOI: 10.2147/ijwh.s108316
|View full text |Cite
|
Sign up to set email alerts
|

Postrape care services to minors in Kenya: are the services healing or hurting survivors?

Abstract: Child sexual abuse is a global problem and a growing concern in Sub-Saharan Africa. It constitutes a profound violation of human rights. To address this problem, Kenya has established the Sexual Offences Act. In addition, Kenya has developed national guidelines on the management of sexual violence to grant minors access to health care. However, little is known about the experiences of sexually abused minors when they interact with the health and legal system. Accordingly, this study uses a triangulation of met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…While treatment for survivors is generally similar for adults and children, the dynamics of dealing with children and adolescents and their needs are vastly different from adults [ 37 ]. A recently published case study found that healthcare providers in Kenya lacked the basic skills necessary to deliver quality services to minors such as obtaining informed consent, maintaining confidentiality, conducting a physical examination that maintains the dignity of the child and collecting specimens [ 38 ]. Our qualitative interviews found that none of the healthcare providers in these facilities had received any training on dealing with children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…While treatment for survivors is generally similar for adults and children, the dynamics of dealing with children and adolescents and their needs are vastly different from adults [ 37 ]. A recently published case study found that healthcare providers in Kenya lacked the basic skills necessary to deliver quality services to minors such as obtaining informed consent, maintaining confidentiality, conducting a physical examination that maintains the dignity of the child and collecting specimens [ 38 ]. Our qualitative interviews found that none of the healthcare providers in these facilities had received any training on dealing with children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Survivors of CSA are either threatened or their parents are given small tokens to settle the cases out of court. 24 Consequently, survivors of CSA tend to disappear from the locality or refuse to testify in law courts. 24 Bail applications need to be evaluated carefully to ensure that state witnesses (CSA survivors and their families) are not intimidated or persuaded into dropping charges.…”
Section: Resultsmentioning
confidence: 99%
“…33 Psychosocial support is poorly administered due to the lack of professionals to offer counselling services. 17 , 24 There is need for Kenyan government commitment to facilitating psychosocial support for survivors of CSA by either training more service providers or contracting services from the private sector.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inability of providers to collect samples from child survivors could be attributed to the lack of protocols for evidence collection as observed in a study conducted in Uganda where only one out of eight hospitals had standardised protocols (Henttonen et al ., ). Findings of this study resonate with existing evidence (Wangamati et al ., ; Welch and Mason, ), highlighting the need for facilities to be stocked with the requisite equipment, supplies and instructional material to aid providers in the collection and documentation of evidence.…”
Section: Discussionmentioning
confidence: 99%